Guillain-Barré Syndrome in a Patient with Metastatic Rectal Cancer Receiving Oxaliplatin-Based Chemotherapy: A Case Report - Sehrish Razzaq; Sadia Abdullah; Esha Khalid (Liaquat National Journal of Cancer Care, 2026)
Oxaliplatin commonly causes peripheral sensory neuropathy, whereas Guillain-Barré syndrome during treatment is rare. We report a 54-year-old man with metastatic rectal cancer who received six three-weekly cycles of capecitabine and oxaliplatin, with a cumulative oxaliplatin dose of approximately 1,230 mg (780 mg/m²). Numbness began after the fifth cycle, followed by progressive weakness after the sixth. Examination showed quadriparesis, areflexia, bilateral foot drop, sensory loss, and muscle wasting. Brain and spine imaging excluded metastasis and cord compression. Cerebrospinal fluid demonstrated albuminocytologic dissociation, while nerve conduction studies showed severe sensorimotor axonal polyneuropathy, consistent with acute motor-sensory axonal neuropathy. Oxaliplatin was discontinued, and five sessions of plasmapheresis improved limb power from 3/5 to 4/5, enabling supported walking. Distal sensory loss and mild wasting persisted at one and three months, indicating partial recovery. Guillain-Barré syndrome should be considered in patients receiving oxaliplatin who develop progressive symmetrical weakness and areflexia rather than conventional chemotherapy-induced sensory neuropathy.